Repeated-sprint ability determined in game in elite male Brazilian football players - Gonçalves da Silva, V.; Cândida Ciriaco Rocha, M. R.; Gonçalves, A. C.; Figueiredo Morandi, R.; Cruz de Oliveira, E.; Mendonça Pimenta, E. (International Journal of Performance Analysis in Sport, 2018)
Purpose: To analyse if the ability of elite Brazilian football athletes to perform repeated sprints, evaluated in real game situations, correlates with their previously determined VO2max. Methods: We analysed data from 10 male elite Brazilian football athletes, who had their movements monitored in the field through GPS devices, during 17 matches of official championships. For analysis of athletes` movements in the field, we considered a block of repeated sprints (BRS), activities characterised by at least 3 sprints with velocity =20 km/h separated by a maximum of 21 s between each sprint. Results: There was no correlation between the ability to perform BRS in real game situations and the previously determined VO2max of athletes (r = 0.5828; p = 0.0770). On the other side, there was a positive correlation between the performance of blocks of repeated sprints and the number of actions within the blocks (r = 0.6712; p = 0.0336), and a negative correlation between the performance of blocks of repeated sprints and the recovery time between one block and another (r = -0.9191; p = 0.0002). Conclusions: Repeated-sprint ability determined in the game in elite male Brazilian football players is not correlated with VO2max.